Apply Canny Detector and Hough Transform For Lane Tracking by Autonomous Type Vehicles - Gurpreet, Kaur; Kaur, Deepinder (International Journal of Computer Sciences and Engineering, 2020)
In this Research we are using canny detector and Hough Transform algorithm for Lane detection. In this research Hough Transformation is use for Find all the edge points in the image using any suitable edge detection scheme and Canny detector for is to detect sharp changes in luminosity (large gradients), such as a shift from white to black, and defines them as edges, given a set of thresholds.